Diversity, Diversification, and Profitability Among British Manufacturing Companies, 1972–1984 - Grant, Robert; Jammine, Azar P.; Thomas, Howard (Academy of Management Journal, 1988)
This study investigated the causal relationships between diversity, diversification, and profitability among 304 large British manufacturing companies that differed in both product and multinational diversity. Diversity and profitability were positively related up to a point; after that point, increases in product diversity were associated with declining profitability. The results were unclear with respect to the underlying causal relationships. Product diversification did not increase profitability, and there was limited evidence that profitability promoted diversification. For multinational diversification, however, we found that profitability in the home market encouraged overseas expansion that in turn increased profitability.